2019
DOI: 10.1186/s12938-019-0623-8
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfields segmentation in brain MR images using generative adversarial networks

Abstract: BackgroundSegmenting the hippocampal subfields accurately from brain magnetic resonance (MR) images is a challenging task in medical image analysis. Due to the small structural size and the morphological complexity of the hippocampal subfields, the traditional segmentation methods are hard to obtain the ideal segmentation result.MethodsIn this paper, we proposed a hippocampal subfields segmentation method using generative adversarial networks. The proposed method can achieve the pixel-level classification of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Since its introduction, there has been a surge of interest in the application of GAN frameworks related to the brain. Some of the applications include image generation with improved properties such as achieving super resolution or better quality [6][7][8][9][10][11], data augmentation [12][13][14], segmentation [9,[13][14][15][16], image reconstruction [17][18][19][20], image-to-image translation [21][22][23][24], and motion correction [25,26]. While these important studies have demonstrated the exciting prospect of using GAN architectures, there is a limited amount of work that has focused on utilizing the generated images for subsequent tasks such as disease classification [27].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction, there has been a surge of interest in the application of GAN frameworks related to the brain. Some of the applications include image generation with improved properties such as achieving super resolution or better quality [6][7][8][9][10][11], data augmentation [12][13][14], segmentation [9,[13][14][15][16], image reconstruction [17][18][19][20], image-to-image translation [21][22][23][24], and motion correction [25,26]. While these important studies have demonstrated the exciting prospect of using GAN architectures, there is a limited amount of work that has focused on utilizing the generated images for subsequent tasks such as disease classification [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, deep learning based methods has been also proposed for hippocampus subfield segmentation. For example, UGNET has been proposed (Shi et al, 2019) using an adversarial training approach and also variants of the famous UNET architecture (Ronneberger et al, 2015) such as the Dilated Dense UNET (Zhu et al,2019) have been proposed. However, one of the major problems of supervised deep learning methods is their hunger for training data to be able to generalize on unseen data.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of the generative and adversarial models enhances the spatial continuity of the segmentation results and improves the accuracy of segmentation. Shi et al [30] proposed a method based on GAN to achieve the hippocampus segmentation. This method uses the UNet network as a generative model and performs interactive training with the adversarial model to achieve pixel-level classification of brain MRI images.…”
Section: Introductionmentioning
confidence: 99%